(untitled) (Nucleus, 2021)
The Brazilian trade balance shows positive surpluses every year, due to the strong performance of the Brazilian agribusiness, which has played a fundamental role in the country’s economy. In view of the economic scenario the peppercorn culture has shown great importance in the Brazilian export market. Considered a commodity this has its transaction carried out through the stock exchange and oscillate through the world market. The present research aims to characterize the chain of black pepper production in the Brazilian scenario. The dynamics of pepper production chain in Brazil is established by its high added value in the product, basically its production is developed by family agriculture, where it shows its strong impact on the maintenance of labor in the field. The Brazilian productivity of black pepper is higher than the world average. However, the initial exploitation of black pepper requires high capital, besides presenting great variability in prices, even though it is a commodity. Being a demanding crop in nutrients and highly susceptible to fusariosis, it is essential to develop alternative exploitation, which can be consortium exploitation, in SAF, besides the technical assistance and organization of producers, to realize sales with volumes and quality in the processing (drying and cleaning) and production of differentiated products, such as white pepper, which has the highest final product value.